2015
DOI: 10.1111/1750-3841.12958
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heavy Meromyosin in Heat‐Induced Gelation in Low Ionic Strength Solution Containing l‐Histidine

Abstract: The gelation of myosin has a very important role in meat products. We have already shown that myosin in low ionic strength solution containing L-histidine forms a transparent gel after heating. To clarify the mechanism of this unique gelation, we investigated the changes in the nature of myosin subfragments during heating in solutions with low and high ionic strengths with and without L-histidine. The hydrophobicity of myosin and heavy meromyosin (HMM) in low ionic strength solution containing L-histidine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Myosin in a low ionic strength solution with l ‐His had a longer and more unravelling rod than native one (Hayakawa et al ., ; Chen et al ., ), which might cause changes in the molecular forces of myosin molecules interaction during gelation (Hayakawa et al ., ). It was indicated that heavy meromyosin (HMM) regions of the myosin in low ionic strength solution with l ‐His could not form disulphide bonds between molecules during heating, resulting in low rigidity of the heat‐induced gel of solubilised myosin (Hayakawa et al ., ). As tail–tail interactions is important in forming the strands and cross‐links that stabilised the gel network, the structural change of the rod regions of myosin in 1 m m NaCl containing l ‐His would affect the interaction between rods during heating (Hayakawa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Myosin in a low ionic strength solution with l ‐His had a longer and more unravelling rod than native one (Hayakawa et al ., ; Chen et al ., ), which might cause changes in the molecular forces of myosin molecules interaction during gelation (Hayakawa et al ., ). It was indicated that heavy meromyosin (HMM) regions of the myosin in low ionic strength solution with l ‐His could not form disulphide bonds between molecules during heating, resulting in low rigidity of the heat‐induced gel of solubilised myosin (Hayakawa et al ., ). As tail–tail interactions is important in forming the strands and cross‐links that stabilised the gel network, the structural change of the rod regions of myosin in 1 m m NaCl containing l ‐His would affect the interaction between rods during heating (Hayakawa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Similar microstructure was also observed in heat‐induced gel of myosin in a low ionic strength solution with l ‐His (Hayakawa et al ., ). The unique gel was reported as the result of low hydrophobicity and/or to the nondecreasing reactive SH content in myosin head interaction (Hayakawa et al ., ) and structural change in myosin rod portion (Hayakawa et al ., ). Compared to that of MPs in 1 m m NaCl, this sponge‐like network induced by l ‐His might be capable to retain more water and hence induce higher water‐binding capacity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During heating, the content of ɑ‐helix and irregular curl in MPs decreased, the content of β‐sheet increased, hydrophobic residues exposed, and the solubility of MPs gradually decreased. (Shimada et al ., 2015; Hayakawa et al ., 2015). In addition, the thermal aggregation or gelation of MPs is affected by attractive and repulsive forces between proteins, which involve hydrophobic and electrostatic interactions, hydrogen bonds, van der Waal's interactions and covalent bonds (Xiong, 1997; Chi et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%